Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-27T20:24:53+01:00
(x-2)-(2-x)=
x-2-2+x=
2x-4


(a+b)+(2a-b)-(a-2b)=
a+b+2a-b-a+2b=
2a+2b


(3x-y+1)-(x+y)+(y-x)=
3x-y+1-x-y+y-x=
x-y+1


-(2a²-3ab)-(2b-3a²)+(-ab-b)=
-2a²+3ab-2b+3a²-ab-b=
a²+2ab-3b
2010-01-27T20:24:53+01:00
(x-2)-(2-x)=x-2-2+x=2x-4
(a+b)+(2a-b)-(a-2b)=a+b+2a-b-a+2b=2a+2b
(3x-y+1)-(x+y)+(y-x)=3x-y+1-x-y+y-x=x-y+1
-(2a²-3ab)-(2b-3a²)+(-ab-b)= -2a²+3ab-2b+3a²-ab-b=a²+2ab-3b
2010-01-27T20:27:30+01:00
A) x-2-2+x=2x-4

b) a+b+2a-b-a+2b= -4b+2a

c)3x-y+1-x-y+y-x= x-y+1

d)-2a²+3ab-2b+3a²-ab-b = a²+2ab-3b